Resistance and survival of endolithic microorganisms in outer space and Mars conditions simulated in space - Scalzi, Giuliano (Università degli studi della Tuscia - Viterbo, 2012)
Dottorato di ricerca in Evoluzione biologica e biochimica Cryptoendolithic microbial communities and epilithic lichens have been considered as appropriate candidates for the scenario of Lithopanspermia, which proposes a natural interplanetary exchange of organisms by means of rocks that have been impact ejected from their planet of origin. So far, the hardiness of these terrestrial organisms in the severe and hostile conditions of space has not been tested over extended periods of time. A first long-term (1.5 years) exposure experiment in space was performed with a variety of rock-colonizing eukaryotic organism at the International Space Station on board of the European EXPOSE-E facility. Organisms were selected that were especially adapted to cope with the environmental extremes of their natural habitat. It was found that some – but not all - of those most robust microbial communities from extremely hostile regions on Earth are also partially resistant against the even more hostile environment of outer space, including high vacuum, temperature fluctuation, the full spectrum of extraterrestrial solar electromagnetic radiation and cosmic ionizing radiation. Colonized Antarctic rocks, retrieved from EXPOSE-E after LIFE experiment, after being plated in MaltAgar medium, showed a development of a green alga and a pink-coloured fungus; they were isolated from a sample exposed to simulated Mars conditions beneath a 0.1% Suprasil neutral density filter and from a sample exposed to space vacuum without solar radiation exposure, respectively. The two organisms able to grow were identified at genus level by Small SubUnit (SSU) and Internal Transcribed Spacer (ITS) rDNA sequencing as Stichococcus sp. (green alga) and Acarospora sp. (lichenized fungal genus) respectively. Moreover, this study has been focused, with a methodological approach, on the new procedures to minimize the biological cross-contamination resulting from the exploration of the solar system. A model microbial community (MMC) of known composition, representative of a typical low-biomass surface sample, was used to examine the effects of variables in sampling matrices, target cell density/molecule concentration, and cryogenic storage on the overall efficacy of the sampling regimen. The MMC used in this study comprised 11 distinct species of bacterial, archaeal, and fungal lineages associated with either spacecraft or clean-room surfaces. The results of this study empower current knowledge of the limits of life on Earth and beyond and hints future molecularanalysis- based microbial sampling and processing methodologies. Comunità microbiche criptoendolitiche e licheni epilitici sono stati considerati come candidati adeguati per lo scenario di Lithopanspermia, che propone uno scambio naturale interplanetario di organismi per mezzo di rocce che sono state espulse dal loro pianeta di origine. Finora, la robustezza di questi organismi terrestri nelle condizioni estremamente ostili dello spazio non è stato testato per periodi di tempo prolungati. Un primo esperimento a lungo termine (1,5 anni) di esposizione nello spazio è stato effettuato con una varietà di organismi eucariotici colonizzatori delle rocce sulla Stazione Spaziale Internazionale a bordo dell’EXPOSE-E facility. I microrganismi che sono stati selezionati, sono particolarmente adattati per far fronte alle condizioni ambientali estreme del loro habitat naturale. È stato riscontrato che alcuni - ma non tutti – quegli organismi delle comunità microbiche provenienti dalle regioni più estreme della Terra, siano parzialmente resistenti all'ambiente ancor più ostile dello spazio esterno e dei suoi parametri, inclusi vuoto, sbalzi di temperatura, l'intero spettro di radiazione solare e radiazioni ionizzanti. Rocce antartiche colonizzate, recuperate da EXPOSE-E dopo l'esperimento LIFE, dopo essere state piastrate sul terreno di cultura MaltAgar, hanno mostrato lo sviluppo di un’ alga verde e un fungo di colore rosa. Sono stati isolati rispettivamente da un campione esposto a condizioni simulate di Marte sotto un filtro a densità neutrale di Suprasil allo 0,1% e da un campione esposto a vuoto spaziale senza esposizione alle radiazioni solari. I due organismi in grado di crescere sono stati identificati a livello di genere mediante sequenziamento dei geni della rRNA Small SubUnit (SSU) e dell’Internal Transcribed Spacer (ITS). I due organismi sono stati identificati come Stichococcus sp. (Alga verde) e Acarospora sp. (genere di fungo lichenizzato). Inoltre, questo studio è stato focalizzato, con un approccio metodologico, sulle nuove procedure per ridurre al minimo la contaminazione incrociata di tipo biologico derivante dalla esplorazione del sistema solare. Una comunità microbica modello (MMC) a composizione nota, rappresentante di una tipica superficie a basso contenuto di biomassa, è stata utilizzata per esaminare gli effetti delle variabili in matrici di campionamento, nello stoccaggio criogenico e sull'efficacia complessiva del regime di campionamento rispetto alle analisi molecolari a valle. La MMC utilizzata in questo studio comprende 11 specie distinte di linee batteriche, archaea, e fungine associate sia con veicoli spaziali che con le superfici di camere sterili. I risultati di questo studio aumentano le conoscenze attuali dei limiti della vita sulla Terra e inoltre e suggeriscono future analisi molecolari basate su campionamento e processamento di campioni biologici provenienti dalle camere sterili dove gli Spacecraft vengono assemblati.